2005
DOI: 10.1128/jvi.79.10.5943-5951.2005
|View full text |Cite
|
Sign up to set email alerts
|

Roles of CD4+T-Cell-Independent and -Dependent Antibody Responses in the Control of Influenza Virus Infection: Evidence for Noncognate CD4+T-Cell Activities That Enhance the Therapeutic Activity of Antiviral Antibodies

Abstract: Previous studies have indicated that B cells make a significant contribution to the resolution of influenza virus infection. To determine how B cells participate in the control of the infection, we transferred intact, major histocompatibility complex class II (MHC-II)-negative or B-cell receptor (BCR)-transgenic spleen cells into B-celldeficient and CD8؉ T-cell-depleted MT mice, termed MT(؊8), and tested them for ability to recover from infection. MT(؊8) mice that received no spleen cells invariably succumbed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 64 publications
5
47
1
Order By: Relevance
“…A recent report from Mozdzanowska et al (49) group also demonstrated that the efficacy of passive Ab transfer was enhanced in the presence of endogenous CD4 cells in a primary response to influenza. In that study, highly purified mAb was injected before infection, and several times thereafter, to promote survival, but the contribution of the CD4 component was not elucidated.…”
Section: Discussionmentioning
confidence: 90%
“…A recent report from Mozdzanowska et al (49) group also demonstrated that the efficacy of passive Ab transfer was enhanced in the presence of endogenous CD4 cells in a primary response to influenza. In that study, highly purified mAb was injected before infection, and several times thereafter, to promote survival, but the contribution of the CD4 component was not elucidated.…”
Section: Discussionmentioning
confidence: 90%
“…This relationship was observed by modifying the vaccine with more antigen or using GLA-SE, and by comparing responses between mouse strains where C57BL/6 mice expressed detectable day 14 antibody titers at lower antigen doses and recovered faster from virus than BALB/c mice. Undoubtedly, CD4 helper T cells are critical in this regard because depletion of this lineage during rH5 priming eliminated antibody production and prevented survival (25,26). Protection may also have been influenced by the induction of cytotoxic CD4 T cells or after CD4-mediated help of killer CD8 T cells (27), although antigen-specific CD8 T cells were not observed in peptide stimulated splenocytes before challenge.…”
Section: Discussionmentioning
confidence: 99%
“…B cell responses importantly contribute to survival from both primary as well as secondary infection with influenza virus (1)(2)(3)(4)(5)(6)(7). Consistent with their role during primary infection, B cell responses in the local draining lymph nodes of the respiratory tract (mediastinal lymph nodes (MLN) 3 ) are induced within 48 -72 h after infection (8), thus around the time of peak lung viral loads.…”
mentioning
confidence: 88%